EVALUATION OF THE TRAINING PROGRAMMES OF THE GHANAIAN FARM INSTITUTES - ASANTE, K. K.; JIBOWO , A. A.; WILLIAMS, S. K. T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
To evaluate the adequacy of the Ghanaian Farm producing proficient agriculturists, 192 students and 160 graduates were studied in 1978. and practical experience were reported as adequate for respondents' job performance. Most training facilities were adequate except water and electricity. No significant relationship was found between farm background age of students and attitude towards agriculture as a progression. Years of formal education of students' parents was significantly related to the occupational aspirations of students. These findings are important in establishing candidate selection, training and government financing policies for the institutes